2020
DOI: 10.2196/14551
|View full text |Cite
|
Sign up to set email alerts
|

Tools for App- and Web-Based Self-Testing of Cognitive Impairment: Systematic Search and Evaluation

Abstract: Background Tools for app- and Web-based self-testing for identification of cognitive impairment are widely available but are of uncertain quality. Objective The objective of this study was to undertake a scoping review of app- and Web-based self-tests for cognitive impairment and determine the validity of these tests. Methods We conducted systematic searches in electronic databases, including Google search, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 27 publications
0
33
0
Order By: Relevance
“…Clinical management of cognitive disorders (ie, managing medical and cognitive problems at home)—for example , educate/assist caregivers in monitoring simple vital signs such as blood pressure, pulse, temperature, blood glucose test, and/or oxygen saturation at home; blood pressure monitoring may be particularly important in limiting further vascular contributions to dementia; oxygen saturation may detect desaturation due to pneumonia/COVID‐19 secure arrangement for medical consultation (via telephone or telemedicine) with general practitioners/specialists to maintain patient care; doctors could make home visits if deemed necessary, but they need to follow infection control measures and put on proper PPE for home visits specialist clinics should triage patients for priority assessment, including assessment of new referrals, 67,68 in particular for those with severe behavioral problems, rapidly progressive cognitive decline, young onset dementia, suspected cases of reversible dementia, or high caregivers’ burden administer cognitive assessment as part of the consultation via telemedicine; 68‐71 note however that the standard norms derived from traditional face‐to‐face assessment may not apply to on‐line assessment 69 conduct simple cognitive assessments (eg, Montreal Cognitive Assessment 5‐minute version) via telephone, 71,72 although there may be challenges, for example, in very impaired or deaf patients consider computerized or online cognitive self‐assessment programs; 73,74 note however that not all versions have been validated 74 remind patients/caregivers to refill and be compliant to prescribed medications; pharmacies should facilitate repeat prescriptions and help coordinate home delivery of medication where relatives are unavailable discuss in advance patients’ and caregivers’ wishes with respect to receiving life‐sustaining treatment including hospitalization, resuscitation, and ventilatory support in the event of respiratory failure due to COVID‐19; ideally, palliative care services should be available in the community 75 use various home sensors in capturing a wide range of health parameters (eg, blood pressure, pulse, temperature, oxygen saturation, heart rhythm, movement, performance in activities of daily living) if such technologies are available 76 …”
Section: Community Home‐based Care Strategiesmentioning
confidence: 99%
“…Clinical management of cognitive disorders (ie, managing medical and cognitive problems at home)—for example , educate/assist caregivers in monitoring simple vital signs such as blood pressure, pulse, temperature, blood glucose test, and/or oxygen saturation at home; blood pressure monitoring may be particularly important in limiting further vascular contributions to dementia; oxygen saturation may detect desaturation due to pneumonia/COVID‐19 secure arrangement for medical consultation (via telephone or telemedicine) with general practitioners/specialists to maintain patient care; doctors could make home visits if deemed necessary, but they need to follow infection control measures and put on proper PPE for home visits specialist clinics should triage patients for priority assessment, including assessment of new referrals, 67,68 in particular for those with severe behavioral problems, rapidly progressive cognitive decline, young onset dementia, suspected cases of reversible dementia, or high caregivers’ burden administer cognitive assessment as part of the consultation via telemedicine; 68‐71 note however that the standard norms derived from traditional face‐to‐face assessment may not apply to on‐line assessment 69 conduct simple cognitive assessments (eg, Montreal Cognitive Assessment 5‐minute version) via telephone, 71,72 although there may be challenges, for example, in very impaired or deaf patients consider computerized or online cognitive self‐assessment programs; 73,74 note however that not all versions have been validated 74 remind patients/caregivers to refill and be compliant to prescribed medications; pharmacies should facilitate repeat prescriptions and help coordinate home delivery of medication where relatives are unavailable discuss in advance patients’ and caregivers’ wishes with respect to receiving life‐sustaining treatment including hospitalization, resuscitation, and ventilatory support in the event of respiratory failure due to COVID‐19; ideally, palliative care services should be available in the community 75 use various home sensors in capturing a wide range of health parameters (eg, blood pressure, pulse, temperature, oxygen saturation, heart rhythm, movement, performance in activities of daily living) if such technologies are available 76 …”
Section: Community Home‐based Care Strategiesmentioning
confidence: 99%
“…High quality digital cognitive assessments that can be administered remotely and asynchronously are urgently needed to meet the growing demand and backlog of patients requiring neuropsychological assessment. While the availability of computerized cognitive assessments has increased rapidly over the past decade ( 3 , 4 ), the clinical validity of these assessments in a remote setting remains a significant issue for both researchers and clinicians. Moreover, the use of computerized cognitive assessments in such unsupervised settings raises an equally important issue regarding environmental validity ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Before EMCT can be deployed at‐scale for research or clinical use, ethical standards and privacy policies need to be in‐place. As evidence of the need for best practices, a recent systematic review found the majority of currently available commercial‐grade app‐based cognitive assessment tools lack any form of validity data (Charalambous et al, 2020).…”
Section: Discussionmentioning
confidence: 99%